2010
DOI: 10.1523/jneurosci.0497-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Monoaminergic Modulation of Sensory-Mediated Aversive Responses in Caenorhabditis elegans Requires Glutamatergic/Peptidergic Cotransmission

Abstract: Monoamines and neuropeptides interact to modulate behavioral plasticity in both vertebrates and invertebrates. In Caenorhabditis elegans behavioral state or "mood" is dependent on food availability and is translated by both monoaminergic and peptidergic signaling in the fine-tuning of most behaviors. In the present study, we have examined the interaction of monoamines and peptides on C. elegans aversive behavior mediated by a pair of polymodal, nociceptive, ASH sensory neurons. Food or serotonin sensitize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 76 publications
4
86
0
Order By: Relevance
“…S6, see supplemental data for structure elucidation). We only detected trace amounts (1-2% of osas#9) of tsas#9 in starved wild-type L1 medium, suggesting that the great abundance of this compound in tbh-1 medium is a result of the roughly 20-fold increased tyramine levels in this mutant (28). These findings demonstrated that osas ascarosides are synthesized from worm-produced octopamine.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…S6, see supplemental data for structure elucidation). We only detected trace amounts (1-2% of osas#9) of tsas#9 in starved wild-type L1 medium, suggesting that the great abundance of this compound in tbh-1 medium is a result of the roughly 20-fold increased tyramine levels in this mutant (28). These findings demonstrated that osas ascarosides are synthesized from worm-produced octopamine.…”
Section: Resultsmentioning
confidence: 69%
“…In C. elegans, octopamine down-regulates pharyngeal pumping (and thereby food intake) as well as egg laying (25,28,30), opposing the effects of serotonin. In addition, octopamine signaling is required for avoidance behavior in response to specific chemical stimuli (29), although octopamine itself is not known to be deterrent.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the neurotransmitters, such as neuropeptides, serotonin (5-HT), tyramine (TA) and octopamine (OA), have been increasingly shown to be transmitters or modulators of ASH-mediated aversive behaviours [12][13][14][15] . ASI sensory neurons are reported to mediate dauer formation 16 , enable worms to learn to avoid the smell of pathogenic bacteria after ingestion via INS-6 signalling 17 , suppress male-specific sexual attraction behaviour 18 , respond to temperature stimuli to negatively modulate thermotaxis behaviour 19 , mediate diet-restriction-induced longevity 20 , modulate satiety quiescence 21 , regulate acute CO 2 avoidance 22 , repress exploratory behaviours that comprise spontaneous reversals and omega turns 5 , and inhibit ASH-mediated aversive responses to 100% 1-octanol 23 .…”
mentioning
confidence: 99%
“…As a result, the mutant features hyperactive motility and hyper-responses as an adult. 34 A representative trajectory of movement over a cycle based on the worm's body centroid is shown in Fig. 6(a).…”
Section: Effects Of Strain and Liquid Viscosity To Motility Changesmentioning
confidence: 99%